Preparation of Porous Ni-Al Alloys and Methane Steam Reforming Application for Hydrogen Generation - Lee, Byung Yong; Jang, Seong-Cheol; Han, Jonghee; Cigolotti, Viviana; Choi, Sun-Hee; Nam, Suk Woo (AMER SCIENTIFIC PUBLISHERS, 2019)
A new alloying method has been proposed to synthesize Ni50Al alloy powder using AlCl3 at 500-600 degrees C under vacuum. AlCl3 served as an activator, promoting the reaction between Ni and Al powders and lowering the fabrication temperature compared with that of conventional synthesis processes. The properties of Ni50Al alloys prepared by varying the synthesis parameters were investigated, and the alloys were alkali leached using NaOH solution for surface modification to increase the specific surface area. Methane steam reforming experiments were performed in the temperature range of 550-850 degrees C investigate the possibility of using the alloys as a catalyst for hydrogen generation. The results confirmed that the leached Ni50Al alloy exhibited good methane conversion, long-term stability without decrease in catalytic activity, and good hydrogen production rate.
Keywords: X-RAY PHOTOELECTRON; CATALYTIC-ACTIVITY; NI3AL POWDER; NICKEL; TEMPERATURE; INTERMETALLICS; SPECTROSCOPY; PASSIVATION; FABRICATION; SURFACES